Child Exploitation of the Character Zain in the Film Capernaum by Nadine Labaki - Sindy Febrianisa; Muhammad Nazar; Fouad Larhzizer (Department of Arabic Education of State Collage for Islamic Studies of Mandailing Natal, 2024)
Zain is the main character in the Capernaum movie directed by Nadine Labaki who described as having a love, devoted, kind, humane character, and not afraid of anything. Based on this, a contracted analysis was carried out on Zain. This research uses a qualitative approach with descriptive methods. The data in this study uses the words, sentences and contexts in this film that are related to Zain. The data source in this study uses a movie entitled